Carbon Dioxide Contamination of Aqueous Morpholine Solutions and Effects on Secondary Coolant Chemistry Under CANDU Conditions. (2nd January 2022) - Fandiño, O.; Cox, J. S.; McGregor, C.; Conrad, J.; Liao, K.; Tremaine, P. R.
Abstract: Exposure to air can cause amine solutions in CANada Deuterium Uranium (CANDU) reactor secondary coolant circuit feed tanks to absorb carbon dioxide (CO2). Likewise, carbon dioxide can be absorbed directly into the amine-containing secondary coolant by air ingress during shutdown, lay-up, and startup. Sampling operations, including transferring the sample to the laboratory and subsequent analyses, can also provide opportunities for CO2 contamination. This paper reports the results of laboratory and chemical modeling studies to examine the effects of CO2 contamination on aqueous morpholine solutions. The chemistry of CO2 uptake by feed tanks containing up to 50 wt% (11.5 mol·kg −1 ) morpholine at 25°C was modeled using the OLI Studio 9.5.2 chemical equilibrium model, and the speciation was confirmed by 13 C nuclear magnetic resonance spectroscopy (NMR) measurements. The effects of CO2 contamination on the pH of the secondary coolant containing 60 ppm (0.006 wt%, 7.00 × 10 −4  mol·kg −1 ) morpholine and the resulting effects on the solubility of magnetite and nickel oxide from 25°C and 250°C at steam saturation were modeled as a function of CO2 loading using the Electrical Power Research Institute chemical modeling software MULTEQ v.8. The chemical modeling calculations show that concentrated alkaline morpholine solutions at room temperature and pressure would be expected to have a strong tendency to absorb CO2 and have additional uptake abilities due to the formation of morpholine carbamates. For dilute morpholine solutions at room temperature and pressure, the solutions are still sufficiently alkaline to absorb enough CO2 to cause a measurable change in the pH of the secondary coolant. This effect was shown to be negligible under reactor operating conditions. The absorption of CO2 would potentially have the most effect on either unprotected feed tanks or during lay-up conditions in the steam generators, as it could depress the pH of the lay-up solution and adversely affect the rate of corrosion in the internal components of the steam generators (e.g., carbon steel materials). The 13 C NMR measurements on samples of 50 wt% aqueous morpholine solutions from feed tanks at the Ontario Power Generation's Pickering Nuclear Generating Station found that CO2 was below the 0.02 wt% detection limit, and suggest that the procedures used to avoid CO2 contamination in feed tanks are effective. The 13 C NMR was shown to be an effective tool for monitoring CO2 uptake by morpholine solution in the feed tanks under conditions in which they may have undergone abnormal exposure to air.